Ecthyma gangrenosum in a child with acute myeloid leukemia. - Presstisa Gifta, Axelia; Nanda Daiva, Putra; Trisiswati , Indranarum; Yuri, Widia; Sawitri, (European Journal of Pediatric Dermatology, 2025)
Ecthyma gangrenosum (EG) is a rare but potentially life-threatening skin infection, most commonly caused by Pseudomonas aeruginosa. It typically affects immunocompromised patients, particularly those with hematologic malignancies and neutropenia. We report a case of EG in a 4-year-old child with acute myeloid leukemia, who developed multiple necrotic skin lesions during hospitalization for febrile neutropenia. This case highlights the importance of early recognition and aggressive management of EG in immunocompromised pediatric patients presenting with rapidly evolving necrotic skin lesions.